2017
DOI: 10.1177/1076029617734309
|View full text |Cite
|
Sign up to set email alerts
|

Use of Guidelines for Reducing Stroke Risk in Patients With Nonvalvular Atrial Fibrillation: A Review From a Latin American Perspective

Abstract: Atrial fibrillation (AF) is a prominent risk factor for stroke and a leading cause of death and disability throughout Latin America. Contemporary evidence-based guidelines for the management of AF and stroke incorporate the use of practical and relatively simple scoring methods to estimate both stroke and bleeding risk, in order to assist in matching patients with appropriate interventions. This review examines consistencies and differences among guidelines for reducing stroke risk in patients with AF, assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 96 publications
0
7
0
1
Order By: Relevance
“…The new Brazilian Guideline from 2016 and Mexican Guidelines, for example, indicates the use of NOACs in a similar manner to the European guidelines. This has also been stressed by different groups of Latin American investigators …”
Section: Discussionmentioning
confidence: 89%
“…The new Brazilian Guideline from 2016 and Mexican Guidelines, for example, indicates the use of NOACs in a similar manner to the European guidelines. This has also been stressed by different groups of Latin American investigators …”
Section: Discussionmentioning
confidence: 89%
“…The variations in the baseline characteristics and antithrombotic treatment patterns for AF are remarkable in different LatAm countries. [ 22 ] Several major guidelines in Latin America including the Brazilian Society of Cardiology 2009, [ 23 ] the Brazilian Cardiogeriatrics Society, [ 24 ] and the Latin-American Society of Cerebrovascular Diseases [ 25 ] recommend the use of vitamin K antagonists for AF stroke prevention. However, there is a significant proportion of high-risk patients receiving no anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on cost-effectiveness comparisons with warfarin have suggested that the use of NOACs in AF patients with moderate to severe risk of stroke is cost-effective. [ 27 , 28 ] Increasing the access to NOACs such as rivaroxaban could help improve the cost allocation. [ 29 ] To our knowledge, we first conducted a meta-analysis of 4 RCTs to determine the efficacy and safety of NOACs with warfarin in LatAm patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…A German guideline 31 states that the efficacy of DOACs has not been proven within less than 14 days after a stroke, but does not make any recommendations on the basis of this statement. We found only guidelines that predated the use of DOACs for Japan (2011), 32 whereas in India 33 and Latin America, 34 ESC, EHRA, and AHA/ASA guidelines are widely used. Repeated brain imaging before starting anticoagulation in patients with moderate and severe stroke to evaluate haemorrhagic transformation is recommended only by the ESC guidelines, 23 without supporting evidence.…”
Section: Guidelinesmentioning
confidence: 99%